Adaptation of the Intelligence Structure Test, Latvian version: psychometric properties - Jokste, Inese; Trups-Kalne, Ingrida; Lubenko, Jelena; Millere, Inga; Kolesnikova, Jelena (Frontiers in Psychology, 2024)
Intelligence-Structure-Test (IST-2000R) (Liepmann et al., 2007) is created to measure reasoning abilities and knowledge through verbal, numerical, and figural domains. The qualities of IST-2000R (Liepmann et al., 2007) have shown its potential to be adapted and standardised in a Latvian sample to be used in psychological evaluation and research, thus satisfying the need for reliable measurement. The aim of this study was to investigate the psychometric properties of the Latvian version of IST-2000R. The adaptation sample consisted of 1017 participants aged 15 to 65 (M=31.8.; SD=10.94) of which 36% were men. Participants were tested using the supervised offline administration mode (exploro.lv). The Ethics Committee of Riga Stradins University (RSU), Riga, Latvia, approved the study. The data show that the psychometric properties of the Latvian version of IST-2000R are in line with scientific norms. Thus, the test is considered to be reliable and may be used for psychological evaluation and research.